Transgenesis and the Study of Expression, Cellular Targeting and Function of Oxytocin, Vasopressin and Their Receptors - Young, 3rd, W. Scott; Gainer, Harold (Neuroendocrinology, 2003)
The neuropeptides oxytocin and vasopressin and the neurons in the hypothalamus that synthesize them have been a rich source for the exploration and understanding of both the brain and the endocrine system. Because of their large size and compact nuclear organization the magnocellular neurons of the hypothalamoneurohypophysial system have traditionally attracted scientists using state-of-the-art techniques, including the subject of this review, transgenesis. We discuss the role of transgenics in deciphering gene elements necessary for the appropriate expression of oxytocin and vasopressin and to deliver exogenous genes, such as green fluorescent protein, selectively to secretory granules in the neurons in the hypothalamoneurohypophysial system. Finally, we review the studies of mice whose genes for oxytocin and, most recently, for the oxytocin and vasopressin receptors have been knocked out through homologous recombination.